Influence Perception Employer Branding and Employer Experience to Turnover Intention Employee in PT. Kalla Arebama - Rubo, Nurfadilla; Saharuddin, Saharuddin; Usman, Halim (PT. EQUATOR SINAR AKADEMIA, 2026)
Study This aim For know influence Perception of employer branding and employer experience on turnover intention of PT Kalla employees Arebama which operates in the 3T sub-district area Rampi , Regency North Luwu . Research use design descriptive quantitative with population as many as 120 employees and samples 92 respondents which is determined through formula Slovin. Collection data done use questionnaire with the Pearson Product Moment validity test and the Cronbach Alpha reliability test which shows all over valid and reliable instruments . Data analysis using multiple linear regression, t-test, F-test, and coefficients determination. Research results show that employer branding and employer experience are partial and simultaneous influential significant towards turnover intention. The more positive perception employee to image company as well as the more Good experience the work they do feel , then the more low intention they For leave work . Coefficient determination show that second variables independent capable explains 75% of the variation in turnover intention, whereas the rest influenced other variables outside research . Findings study This confirm that success company in suppress turnover no only determined by compensation , but also by reinforcement image company as place interesting work​ as well as creation experience positive and meaningful work​ for employee .